ANALISIS PERSEPSI SISWA TERHADAP PELAKSANAAN GERAKAN LITERASI SEKOLAH DI SD NEGERI 110 PEKANBARU - Tiara Yulia Putri; M. Jaya Adi Putra; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrac: The goal of this study is describe literacy movement in SD Negeri 110 Pekanbaru. This study was a descriptive quantitative. The population of this study was all students of class IV and class V of SD Negeri 110 Pekanbaru with a total population of 230 students. The samples in this research using propotional random sampling technique that can be known the total research sample 60 students. The data collection technique used is questionnaire. While the data analysis technique used is descriptive statistics by calculating the percentage of students' perceptions for each sub-indicator. The overall results of the study were tabulated and the percentage with the results of students' perceptions of the implementation of literacy movements in elementary schools is in the category of very good perception. This can be seen in the acquisition of the percentage of students' perceptions based on sub-indicators namely, giving a picture of 85.07%, giving responses of 82.98%, impressions in the brain of 84.24%, knowledge and understanding of 86.59%, assessment from individuals as much as 84.52% and compare understanding gained as much as 85.48%.Key Words: Student Perceptions, School Literacy Movements.